2021
DOI: 10.31573/eksos.v17i1.342
|View full text |Cite
|
Sign up to set email alerts
|

Penilaian Alternatif pada Keterampilan Berbicara Bahasa Inggris di Sekolah Menengah Kejuruan Kota Pontianak

Abstract: English speaking skill is an important communication skill and must be mastered by students to be able to interact actively, convey ideas and provide responses in both formal and informal situations. Alternative assessment provides benefits for students and teachers in improving students' speaking skill in English. This research focuses on an alternative assessment of English speaking skill in Vocational High Schools in Pontianak City, especially South Pontianak. The objectives of this research are (1) to dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Similarly, Listiyawati et al (2021) found that performance-based and peer assessments, as well as portfolios, were mainly used to assess students' skills. Furthermore, Rukmini and Saputri (2017), on the authentic assessment to measure students' productive English skills based on the 2013 curriculum, found that English skills, such as speaking, were assessed through performance with the system using a rubric.…”
Section: Methods Used In Assessing Attitude Knowledge and Skillsmentioning
confidence: 99%
“…Similarly, Listiyawati et al (2021) found that performance-based and peer assessments, as well as portfolios, were mainly used to assess students' skills. Furthermore, Rukmini and Saputri (2017), on the authentic assessment to measure students' productive English skills based on the 2013 curriculum, found that English skills, such as speaking, were assessed through performance with the system using a rubric.…”
Section: Methods Used In Assessing Attitude Knowledge and Skillsmentioning
confidence: 99%